Molecular simulation of hydrocarbon adsorption in transition-metal-modified zeolites for controlling natural gas engine cold-start emissions - Yuyu Li; Chuanfu Kou; Jiaqiang E; Dezhong Ning; Yan Tan; Changling Feng; Chen Xiang (Fuel, 2026)

A deep learning framework for mitigating agricultural pollution: Quantifying and managing herbicide drift risk to non-target crops from UASS spraying - Huiyuan Zhang; Tongye Shi; Xiaofu Feng; Ziyan Liu; Zhaoyan Zhu; Mengran Yang; Changling Wang; Xiongkui He (Journal of Cleaner Production, 2025)

Investigation on performance enhancement and emission reduction of micro methanol steam reforming hydrogen reactor for proton exchange membrane fuel cell - Bo Luo; Jiaqiang E; Changling Feng; Xinyu Song; Jiangjun Ding; Wenming Yang (Journal of Cleaner Production, 2025)

Identification of stable reference genes for qPCR analysis of gene expression in Oocystis borgei under various abiotic conditions - Ning Zhang; Jiajia Ren; Ting Hong; Zhongdian Dong; Feng Li; Yulei Zhang; Xianghu Huang; Changling Li; Zhangxi Hu (Algal Research, 2025)

Genomic analysis of modern maize inbred lines reveals diversity and selective breeding effects - Kaijian Fan; Mohsin Ali; Kunhui He; Yingwei Feng; Tingxi Yu; Hao Zhang; Tai An; Weiwei Zeng; Junjie Fu; Ying Zhou; Yanfang Heng; Fei Gu; et al. (Science China Life Sciences, 2025)

Dependence of the hydrate-based CO2 storage characteristics on sand particle size and clay content in unconsolidated sediments - Jiaxian Wang; Yunkai Ji; Changling Liu; Fulong Ning; Qingguo Meng; Yapeng Zhao; Jing Li; Zhun Zhang; Yongchao Zhang; Feng Cai (Chemical Engineering Journal, 2024)

Effects of salinity on the growth, physiological and biochemical components of microalga Euchlorocystis marina - Yao Pan; David Kwame Amenorfenyo; Mingbiao Dong; Ning Zhang; Xianghu Huang; Changling Li; Feng Li (Frontiers in Marine Science, 2024)
Euchlorocystis marina , a new marine species of the genus Euchlorocystis discovered in 2022, has the potential to improve the water quality in mariculture ponds. However, the effects of salinity on the growth, physiology, and biochemical composition of these algae are not well understood. In this study, changes in physiological and biochemical indices such as cell density, photosynthetic pigment, polysaccharide, and lipid content of E. marina under different salinity treatments were analyzed. The results showed that the highest cell density was observed at a salinity of 15‰. The lowest photosynthetic pigment content was observed at a salinity of 60‰, and the highest polysaccharide and lipid content was observed at a salinity of 60‰. These results indicated that lower salinity was more conducive to E. marina reproduction and growth. E. marina can accumulate polysaccharides and lipids in high salinity environments. This study provides new information for understanding the salinity adaptation strategies of E. marina and has practical significance for its development and utilization.

Survey of the biogenic amines in typical foods commonly consumed from the Chinese market - Xuan Zhang; Changling Fang; Xiaoyi Lou; Feng Han; Siman Li; Yongfu Shi; Dongmei Huang (Food Control, 2024)

Characteristics of arsenic speciation in mainly cultured shellfish from Sanmen Bay, Zhejiang Province, China - Maoxia Ran; Yongfu Shi; Di Wu; Hongli Ye; Dongsheng Feng; Dongmei Huang; Siman Li; Changling Fang (Marine Pollution Bulletin, 2023)

Longitudinal expression profiles of flavonoid synthesis-related genes and their correlations with contents of flavonoids including anthocyanins in purplish-green aerial stems of Panax notoginseng - Hongling Zhang; Guiqiong Li; Min Jiang; Changling Zhao; Pengyu Zhao; Chen Wang; Guosong Wen; Feng Zhou; Wenhua Dongchen; Shaozhong Xu; Ting Mu; Fanlai Meng; et al. (Acta Physiologiae Plantarum, 2023)

Effects of Nitrogen and Light Intensity on the Astaxanthin Accumulation in Motile Cells of Haematococcus pluvialis - Feng Li; Minggang Cai; Yanqi Wu; Qingsheng Lian; Zuyuan Qian; Jiansen Luo; Yulei Zhang; Ning Zhang; Changling Li; Xianghu Huang (Frontiers in Marine Science, 2022)
The dietary supplementation of Haematococcus pluvialis is a natural, safe, and sustainable method for fish pigmentation. However, astaxanthin-rich H. pluvialis cysts have a poor effect in pigmenting salmonid flesh due to their rigid and thick cell wall. H. pluvialis thin-walled motile cells have recently attracted attention due to their potential advantages in maintaining compound stability, easy digestion, enhancing the bioavailability of carotenoids, and reducing production costs. This study aimed to investigate the effect of various nitrogen concentrations and light intensities on astaxanthin production in motile cells. We first investigated the effect of four different concentrations of nitrogen on astaxanthin accumulation in motile cells. According to the results, the motile cells had the highest astaxanthin concentration and content under the 0 N condition. Then, we compared the differences in astaxanthin production in motile cells under three different light intensities under 0 N conditions. The results showed that after four days of treatment, the protoplasts of the motile cells in the medium light (ML) group and the high light (HL) group had distinct granularity. The cell mortality rate in the HL group reached more than 15%, which was significantly higher than that in the low light (LL) and ML groups, indicating that high light intensity was not suitable for inducing motile cells to accumulate astaxanthin. There were no significant differences between the LL and ML groups in astaxanthin content, motile cells percentage, and cell mortality rate. Considering these indicators, we recommended inducing motile cells to produce astaxanthin under low light conditions because it is more economical in terms of electricity consumption. This study added to the knowledge that nitrogen and light affects the accumulation of astaxanthin in H. pluvialis motile cells. The results would help determine the optimal nitrogen and light conditions in astaxanthin production from motile cells.

The Variation of Microbial (Methanotroph) Communities in Marine Sediments Due to Aerobic Oxidation of Hydrocarbons - Jing Li; Changling Liu; Nengyou Wu; Xingliang He; Xiluo Hao; Feng Li; Ye Chen; Qingguo Meng (Journal of Ocean University of China, 2021)

Complete Genome Sequence Analysis of Brevibacillus laterosporus Bl-zj Reflects its Potential Algicidal Response - Yulei Zhang; Dong Chen; Jian Cai; Ning Zhang; Feng Li; Changling Li; Xianghu Huang (Current Microbiology, 2021)